A DESCARACTERIZAÇÃO DO SISTEMA DE DOMÍNIO IMPERIAL ROMANO NO OCIDENTE - Mendes, Norma Musco (PHOÎNIX, 2020)
The purpose of this paper is to stress that for the study of the process of desintegration of the Roman Empire it is important the analysis of the social dynamic of the roman-germanic relations. This relationship explains the decisive change within the social and political framework of the communities further to the north in the germanic hinterland from I to IV century A. D.